A Legal Analysis of the Independence of the Prosecutorial System: A Comparative Study between the United States and Indonesia. - Dativa Wilma Azali azali; Arif Hidayat Hidayat (Law Research Review Quarterly, 2026)
The independence of the prosecutor’s office constitutes an essential element in a democratic rule of law because the institution exercises strategic authority in determining prosecution policy and implementing criminal law enforcement. Differences in constitutional structure, legal traditions, and political systems influence how prosecutorial independence is designed and practiced across countries. This article examines the independence of prosecutorial institutions in Indonesia and Amerika Serikat through a comparative constitutional law approach by analyzing institutional status, prosecutorial powers, legal principles, and mechanisms of accountability within each legal system. The research applies normative legal methods using statutory, conceptual, and comparative approaches, supported by primary, secondary, and tertiary legal materials analyzed qualitatively through deductive and comparative reasoning. The findings show that prosecutorial independence includes structural, functional, and personal dimensions. In Indonesia, functional independence is formally recognized, yet structural and personal independence remain limited due to the prosecutor’s institutional placement within the executive branch and the hierarchical nature of prosecutorial authority. In contrast, the United States demonstrates relatively stronger structural and functional independence through federal institutional design, decentralized prosecution, and constitutional checks and balances, although risks of politicization remain in certain contexts. Strengthening constitutional guarantees, accountability mechanisms, and merit-based professional systems is therefore necessary to reinforce prosecutorial independence in Indonesia as part of broader democratic legal reform.